Konsep Kewirausahaan Dalam Konteks Pilihan Karir Seorang Muslim - Utari Evy Cahyani (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
Education is considered as a mean to improve the quality of human resources itself. A good education are expected to provide the high quality human resources. But in reality today, education is also considered to be closely related to unemployment, especially unemployment of well educated labor. Seen from the number of people working with university education just as much as 8.8 million people. Based on these data clearly illustrate the ironic, where the higher a person's education, the higher probability of him being unemployment. Given the magnitude of the benefits that can be gained through entrepreneurship, especially to improve the quality of life and quality of individual, then entrepreneurship needs to be maintained as an alternative career choice of a Moslem. Why always depend on others while we have been provided by Allah SWT variety of potential which can be used for standalone or even job opportunities for others. Our task is how to recognize potential that exists and use it in startup business.